A Study on Vertebral Compression Fracture in Postmenopausal Women with Back Pain in Two Medical College Hospitals of Bangladesh - Anam, Khairul; Tazri, Sumia Ahmed; Faiza, Fairzu; Raza, AKM Maruf (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: To determine the prevalence and nature of the vertebral compression fracture in postmenopausal women suffering from back pain in the rural communities of Bangladesh. Materials and methods: Cross sectional study was conducted for the period January to December 2018 which included all postmenopausal women aged 55 years and above presented with back pain in the Obstetrics and Gynaecology and Orthopedic outpatient Departments of Jahurul Islam Medical College and North Bengal Medical College Hospitals. Vertebral fractures were diagnosed by X-Ray scanning of the spine based on predefined criteria. Results: Prevalence of vertebral compression fracture was 30.6%. Most of the subjects were highly active, of poor nutritional status and undergraduate. Majority (35.7%) of the patients belonged to 55-59 years group but prevalence was highest in 70-75 years of age. Maximum patients (48.1%) sustained fracture at only one vertebra. Highest number of fracture (61.1%) was found in the dorsolumbar region. Most of the fracture (44.8%) was of biconcave shape. Most of the wedge deformities were present from 12th thoracic and above and majority of the biconcave deformities were from 11th thoracic and below. Conclusion: Although the prevalence was low in comparison to other studies, it showed a great burden on our social life. The most important step in treating vertebral compression fractures is prevention and treatment of osteoporosis. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 49-53